The Milky Way Rotation Curve Revisited. (2nd October 2018) - Krełowski, J.; Galazutdinov, G.; Strobel, A.
Abstract: The paper revisits the problem described in detail in our Paper I (Galazutdinov et al.3 ) concluding that the rotation curve of the thin gaseous Galactic disk, represented by the Caii lines, is Keplerian outside the solar orbit rather than flat. Now we apply new trigonometric Gaia parallaxes, published in the Data Release 2. We demonstrate that the distances, measured using Gaia parallaxes and Caii column densities, coincide statistically without systematic difference. Consequently, the result shown in Paper I is confirmed: the orbital motion of Galactic translucent clouds is not affected by hypothetical dark matter.